Titanium Alloys in Surgical Implants 1983
DOI: 10.1520/stp28937s
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Loading Behavior of Femoral Stems of Ti-6Al-4V and Cobalt-Chromium Alloys: A Three-Dimensional Finite Element Analysis

Abstract: Large stiff, small moderately stiff, and small flexible femoral total hip components cemented in the proximal femur have been investigated using a three-dimensional finite element model and validated using experimental strain gage techniques. A physiological load of three times body weight (2000 N), 18 deg from vertical was utilized to compute stresses in the bone, cement, and metal construct. For a well-fixed total hip replacement, the results show stem stresses to be between 5 and 20 percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…22,26 Theoretically, less stiff implants reduce stress within the stem and transfer load over a greater area of the cortical bone. 43,44 In our study, comparison of similar titanium and chromium-cobalt implants showed that the stiffness of the implant had no significant effect on micromovement at the cement-bone interface. Furthermore, the two stems presented comparable lower peak values for shear stress at this site.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…22,26 Theoretically, less stiff implants reduce stress within the stem and transfer load over a greater area of the cortical bone. 43,44 In our study, comparison of similar titanium and chromium-cobalt implants showed that the stiffness of the implant had no significant effect on micromovement at the cement-bone interface. Furthermore, the two stems presented comparable lower peak values for shear stress at this site.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore cobalt-chromium seems to be the best material for THA. Previous numerical models 43,44 have shown, however, that a cobalt-chromium stem unloads the proximal femur to a higher degree than a titanium stem and that this may enhance stress-shielding. 22,26 Theoretically, less stiff implants reduce stress within the stem and transfer load over a greater area of the cortical bone.…”
Section: Discussionmentioning
confidence: 98%
“…In the work by Semlitsch et al [36] published in the ASTM STP796, a rotating bending fatigue strength of 400 MPa was reported to be the minimum requirement of hot-forged Ti-6Al-4V for hip implants. Tarr et al [37] reported in the same ASTM publication the fatigue stress value of 550 MPa as a failure criterion for a Ti-6Al-4V alloy to be employed in femoral stems. These values are nearly within the same range pointed out by Potomati et al [34] when Fig.…”
Section: Changing the Surface Roughnessmentioning
confidence: 99%
“…Obwohl die Zementiertechniken und die Prothesen inzwischen erheblich verbessert werden konnten, zählt noch immer die frühzeitige aseptische Lockerung des Schaftes zu den Hauptproblemen. Die Ursachen für diesen massiven Knochenabbau werden sowohl in der toxischen Wirkung von nicht auspolymerisierten Monomeren des Knochenzementes [92] als auch in der Störung der Blutversorgung durch den Zementköcher [7,9] vermutet, vor allem der unphysiologischen Belastung des Knochens unterhalb der Re-sektionsebene nach dem Prinzip der funktionellen Anpassung zugeschrieben [4,18,22,45,51,49,69,72,71,81,84,94,95,9,41,21]. Einerseits wird die Schwachstelle des zementierten künstlichen Hüftgelenks im Knochenzement gesehen und daraus gefolgert, daß alle Maßnahmen, die den Knochenzement proximal medial entlasten, die Lebenserwartung des Gelenkersatzes erhöhen [12,13,15].…”
Section: Introductionunclassified
“…Die Ursachen für diesen massiven Knochenabbau werden sowohl in der toxischen Wirkung von nicht auspolymerisierten Monomeren des Knochenzementes [92] als auch in der Störung der Blutversorgung durch den Zementköcher [7, 9] vermutet, vor allem der unphysiologischen Belastung des Knochens unterhalb der Re-sektionsebene nach dem Prinzip der funktionellen Anpassung zugeschrieben [4,18,22,45,51,49,69,72,71,81,84,94,95,9, 41,21].Dieser Beitrag befaßt sich mit den wichtigsten aktuellen Fragen im Zusammenhang mit der Zementprothese. Aufgrund des unterschiedlichen -Moduls von Ti-und CoCr-Legierungen kommt es zu verschiedenen Krafteinleitungscharakteristiken in das proximale Femur.…”
unclassified